The Dialectics of Metacognition and Spirituality: Integrating Self-Regulated Learning within the Islamic Intellectual Tradition - Ahmad Muzakkil Anam; Alparslan Acikgenc; Moh Irsyad Fahmi MR; Noor Alwiyah (Program Studi Pendidikan Agama Islam - Universitas Negeri Yogyakarta, 2026)
In the 21st-century educational landscape, the focus has shifted from content acquisition to the mastery of